High-throughput RNAi screening identifies a role for the osteopontin pathway in proliferation and migration of human aortic smooth muscle cells - Zhang, Lei; Erfle, Holger; Harder, Nathalie; Beneke, Jürgen; Beil, Nina; Bulkescher, Ruben; Rohr, Karl (Cardiovascular drugs and therapy, 2016)
PurposeUnderstanding of the mechanisms of vascular smooth muscle cells (VSMCs) phenotypic regulation is critically important to identify novel candidates for future therapeutic intervention. While HTS approaches have recently been used to identify novel regulators in many cell lines, such as cancer cells and hematopoietic stem cells, no studies have so far systematically investigated the effect of gene inactivation on VSMCs with respect to cell survival and growth response.Methods and Results257 out of 2000 genes tested resulted in an inhibition of cell proliferation in HaoSMCs. After pathway analysis, 38 significant genes were selected for further study. 23 genes were confirmed to inhibit proliferation, and 13 genes found to induce apoptosis in the synthetic phenotype. 11 genes led to an aberrant nuclear phenotype indicating a central role in cell mitosis. 4 genes affected the cell migration in synthetic HaoSMCs. Using computational biological network analysis, 11 genes were identified to have an indirect or direct interaction with the Osteopontin pathway. For 10 of those genes, levels of proteins downstream of the Osteopontin pathway were found to be down-regulated, using RNAi methodology.ConclusionsA phenotypic high-throughput siRNA screen could be applied to identify genes relevant for the cell biology of HaoSMCs. Novel genes were identified which play a role in proliferation, apoptosis, mitosis and migration of HaoSMCs. These may represent potential drug candidates in the future.